2014
DOI: 10.1039/c4cp00144c
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of crystal water with the building block in Y2Mo3O12 and the effect of Ce3+ doping

Abstract: Ce(3+) ions are introduced into the lattice of Y2Mo3O12 with a sol-gel method with the aim to reduce its hygroscopicity and pursue the interaction of crystal water molecules with the building block. It is found that Ce(3+) ions occupy the positions of Y(3+) in the lattice and have the function of expelling crystal water molecules in the microchannels so that the number of crystal water molecules decreases significantly as the Ce(3+) content increases and a complete depletion of the crystal water is achieved wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 27 publications
(47 reference statements)
1
37
0
Order By: Relevance
“…Figure 1a shows the relative linear length change curves of Y 2− x Zr x Mo 3− x V x O 12 (0.0 ≤ x ≤ 1.4). For the sample with x = 0.1 in Y 2− x Zr x Mo 3− x V x O 12 , the thermal expansion property was similar to the reported Y 2 Mo 3 O 12 ( x = 0.0) [22,23], indicating that less substitution of Zr/V for Y/Mo in Y 2 Mo 3 O 12 could not change the crystal structure of Y 2 Mo 3 O 12 . However, for x = 0.3, the thermal contraction and thermal expansion corresponding to the release of adsorbed and crystal water before 476 K reduced remarkably, indicating obvious reduction of the hygroscopicity (Figure 1b) [29].…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…Figure 1a shows the relative linear length change curves of Y 2− x Zr x Mo 3− x V x O 12 (0.0 ≤ x ≤ 1.4). For the sample with x = 0.1 in Y 2− x Zr x Mo 3− x V x O 12 , the thermal expansion property was similar to the reported Y 2 Mo 3 O 12 ( x = 0.0) [22,23], indicating that less substitution of Zr/V for Y/Mo in Y 2 Mo 3 O 12 could not change the crystal structure of Y 2 Mo 3 O 12 . However, for x = 0.3, the thermal contraction and thermal expansion corresponding to the release of adsorbed and crystal water before 476 K reduced remarkably, indicating obvious reduction of the hygroscopicity (Figure 1b) [29].…”
Section: Resultssupporting
confidence: 73%
“…Figure 2c shows the Raman spectra of Y 2− x Zr x Mo 3− x V x O 12 . For x = 0.1, there were three primary Raman bonds similar to 940, 821, and 334 cm −1 and that of Y 2 Mo 3 O 12 , due to the presence of crystal water [22,23,25]. Additionally, two weak peaks at 258 and 887 cm −1 were also detected, which should have been related to Zr-O or V-O vibrations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since most materials expand on heating and contract on cooling, materials with opposite property, namely negative thermal expansion (NTE), are particularly desired for tailoring CTEs. The rediscovery of NTE in ZrW 2 O 8 in a wide temperature range (Evans et al, 1996, 1997a) triggered continuous efforts on understanding the NTE phenomenon and searching for more NTE materials (Yang et al, 2007; Chen et al, 2013, 2015; Tallentire et al, 2013; Lama et al, 2014; Liu et al, 2014; Peng et al, 2014; Xiao et al, 2014; Hu et al, 2015). To date, different families of NTE materials based on various mechanisms, such as the phonon effect (Pryde et al, 1996; Wang et al, 2011; Bridges et al, 2014; Cheng et al, 2016a; Ge et al, 2016a), magnetovolume effect (Takenaka and Takagi, 2005; Qu et al, 2012; Yan et al, 2014), spontaneous ferroelectric polarization (Chen et al, 2013; Peng et al, 2016), and charge transfer (Long et al, 2009; Azuma et al, 2011; Yamada et al, 2016) have been reported.…”
Section: Introductionmentioning
confidence: 99%